Ambidexterity as Historically Embedded Process: Evidence From NASA, 1958 to 2016. (June 2019) - Heracleous, Loizos; Yniguez, Carlos; Gonzalez, Steven A.
Even though the growing ambidexterity literature has delivered useful insights, this theme has been researched largely in static and a-contextual terms, without adequate attention to how an organization's history and context can shape its present. In this article, we employ NASA (National Aeronautics and Space Administration) as an in-depth case study to trace how its historical trajectory has shaped its current propensity to be ambidextrous. Our study reveals organizational ambidexterity as a path-dependent, contingent process rather than something necessarily achievable via the more generic prescriptions of structural, temporal, or contextual ambidexterity models.